Advanced Targeted, Cell and Gene-Therapy Approaches for Pediatric Hematological Malignancies: Results and Future Perspectives - Magnani, Chiara F.; Tettamanti, Sarah; Maltese, Francesca; Turazzi, Nice; Biondi, Andrea; Biagi, Ettore (Frontiers in Oncology, 2013)
Despite the survival of pediatric patients affected by hematological malignancies being improved in the last 20 years by chemotherapy and hematopoietic stem cell transplantation (HSCT), a significant amount of patients still relapses. Treatment intensification is limited by toxic side effects and is constrained by the plateau of efficacy, while the pipeline of new chemotherapeutic drugs is running short. Therefore, novel therapeutic strategies are essential and researchers around the world are testing in clinical trials immune and gene therapy approaches as second-line treatments. The aim of this review is to give a glance at these novel promising strategies of advanced medicine in the field of pediatric leukemias. Results from clinical protocols using new targeted “smart” drugs, immunotherapy and gene therapy are summarized, and important considerations regarding the combination of these novel approaches with standard treatments to promote safe and long-term cure are discussed.